Do fluoroquinolones increase aortic aneurysm or dissection incidence and mortality? A systematic review and meta-analysis - Chen, Can; Patterson, Benjamin; Simpson, Ruan; Li, Yanli; Chen, Zhangzhang; Lv, Qianzhou; Guo, Daqiao; Li, Xiaoyu; Fu, Weiguo; Guo, Baolei (Frontiers in Cardiovascular Medicine, 2022)
Objectives: To determine the association between fluoroquinolones (FQs) use, the risk of de novo aortic aneurysm or dissection (AAD), and the prognosis of patients with pre-existing AAD. Methods: We searched PubMed, EMBASE, CENTRAL, Scopus and Web of Science on March 31th, 2022. Observational studies which evaluated the association of FQs with AAD risk in the general population, or FQs with the prognosis of patients with pre-existing AAD and presented adjusted effect estimates were included. Two reviewers assessed study eligibility, extracted data, and assessed risk of bias and certainty of evidence using GRADE. Results: Of the 13 included studies, eleven focused on the association of FQs with de novo AAD incidence, and only one on the association of FQs with AAD patient prognosis. FQ use was associated with an increased risk of de novo AAD within 30-day (RR 1.42; 95%CI, 1.11 to 1.81; very low certainty) and 60-day (RR 1.44; 95%CI, 1.26 to 1.64; low certainty). Specifically, the association was significant when compared with amoxicillin, azithromycin, doxycycline, or no antibiotic use. Furthermore, patients with pre-existing AAD exposure to FQ had an increased risk of all-cause mortality (RR: 1.61; 95% CI: 1.50 to 1.73; moderate certainty) and aortic-specific mortality (RR: 1.80; 95%CI: 1.50 to 2.15; moderate certainty), compared to the non-exposed FQ group within a 60-day risk period. Conclusions: FQs were associated with an increased incidence of AAD in general population and a higher risk of adverse outcomes in patients with pre-existing AAD. Nevertheless, the results may be affected by unmeasured confounding factors. This should be considered by physicians contemplating using FQs in patients with aortic dilation and those at high risk of AAD.